Negotiating Policy, Culture, and Conviction: The Role of Teacher Beliefs in Language Education - Lestari, M. Nirmala; Ihsan, Pramudana (Lingua : Journal of Linguistics and Language, 2024)
This study presents a narrative review of the role of teacher beliefs in language education and their influence on pedagogical practices. The review aimed to synthesize current research to identify how teacher cognition interacts with contextual factors such as policy, culture, and institutional support. A systematic search was conducted across databases including Scopus, Web of Science, ERIC, and Google Scholar using keywords such as teacher beliefs, pedagogical practices, EFL teaching, ESL methodologies, multilingual education, and professional development. Inclusion criteria focused on peer-reviewed studies published between 2010 and 2025. The literature revealed that teacher beliefs significantly shape the adoption of strategies like task-based learning and communicative approaches, although their enactment is often constrained by standardized curricula and assessment policies. Social and cultural contexts strongly mediate these dynamics, with teachers in developed contexts more likely to realize student-centered practices than those in resource-limited systems. Positive beliefs toward technology integration were widespread but frequently undermined by inadequate training and infrastructure. Professional development was consistently highlighted as an effective mechanism for transforming teacher beliefs and aligning them with innovative pedagogies. The discussion emphasizes the systemic barriers—including workload, rigid evaluation frameworks, and limited support—that hinder teachers from implementing their convictions. The findings suggest the need for flexible policy frameworks, increased institutional support, and targeted training to bridge the gap between teacher beliefs and pedagogical practices. Future research should pursue longitudinal and comparative studies to further explore these relationships and their impact on student learning outcomes.